2017
DOI: 10.1039/c7nr03419a
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved nanomechanics of a single cell under the depolymerization of the cytoskeleton

Abstract: Single cell stiffness measurements consider cells as passive and elastic materials which react instantaneously to an external force. This approximation is at odds with the complex structure of the cell which includes solid and liquid components. Here we develop a force microscopy method to measure the time and frequency dependencies of the elastic modulus, the viscosity coefficient, the loss modulus and the relaxation time of a single live cell. These parameters have different time and frequency dependencies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 57 publications
2
51
0
Order By: Relevance
“…Several FDC experiments have revealed that the approach and retraction sections of force-distance curves performed on mammalian cells do not overlap. 3,41,50 The hysteresis observed in a FDC is either a consequence the existence of energy-dissipation processes inside a material 59,60 or produced by the breaking of the plasma membrane. Force-distance curves acquired sequentially on a single cell are very reproducible, 3,41 therefore, we conclude that the hysteresis is dominated by dissipative processes occurring inside the cell.…”
Section: Mechanical Model Of a Living Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Several FDC experiments have revealed that the approach and retraction sections of force-distance curves performed on mammalian cells do not overlap. 3,41,50 The hysteresis observed in a FDC is either a consequence the existence of energy-dissipation processes inside a material 59,60 or produced by the breaking of the plasma membrane. Force-distance curves acquired sequentially on a single cell are very reproducible, 3,41 therefore, we conclude that the hysteresis is dominated by dissipative processes occurring inside the cell.…”
Section: Mechanical Model Of a Living Cellmentioning
confidence: 99%
“…31,32 Living cells show a variety of viscoelastic phenomena which remain insufficiently understood. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] This lack of understanding has fundamental and practical implications. The accuracy of Young's modulus measurements determined without considering viscoelastic effects is highly questionable.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In mechanobiology, there is some evidence that supports the influence of the cell's viscoelastic processes in its physiology. [14][15][16][17] However, the interpretation of the AFM data in terms of the viscoelastic parameters of the sample is quite challenging. Among other issues, there is no established and generally accepted framework to measure the viscoelastic properties from AFM experiments.…”
Section: Introductionmentioning
confidence: 99%
“…This viscosity is mostly related to the compressive viscoelastic coefficient (also known as the Trouton coefficient) because indentation measurements involve application of compressive forces normal to the sample surface [30]. The analytical solution (eq.…”
Section: Simplest Spring-dashpot Combinationsmentioning
confidence: 99%